Um mecanismo de descoberta sensível ao contexto de objetos inteligentes em Internet das Coisas - Barreto, Felipe Mota; Viana, Windson; Andrade, Rossana Maria de Castro (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
In the Internet of Things vision, smart objects are interconnected providing applications at everyday life places (e.g., house, cars, school, buildings). The number of smart objects will increase every year, which creates a need for contextual discovery services of those devices and their provided services. Web based protocols are widely used by IoT applications to interact with smart objects, among them, the most used is the CoAP protocol. This work presents a discovery mechanism that uses contextual information to select the things that are relevant to the user or to the system itself. To perform the discovery, the mechanism extends the default discovery service from CoAP, adapting it to the new IoT requirements while keeping the Web compatibility provided by CoAP.